Wireless Sensor Network Based Server Room Temperature Monitoring System - Reza Nandika; Era Madona; Laxsmy Devy; Adi Chandranata; Yultrisna Yultrisna (JECCOM: International Journal of Electronics Engineering and Applied Science, 2023)
A remote temperature monitoring system has been created in the server room using LoRa technology which is based on preventing overheating on servers which can affect the performance of components in the server. The research objective is to design and implement a new LoRa-based server room monitoring system design. The targets of this research are (a) creating a system prototype, (b) programming the system with the help of Arduino IDE, (c) measuring system performance. The research method starts from making a prototype and measuring system performance. The results of system performance measurements, testing on LoRa showed the best RSSI results of -56 dBm, temperature data from 17°C -19°C and humidity from 55% to 59% in the server room. Overall the tool can function well.